Numerical Simulation and Experimental Study on Construction Forming of Cable-Stayed Tensioned Metal Thin Sheet Structure - Jie Qin; Shuo Xiao; Guojun Sun; Dehai Feng; Jinzhi Wu (Buildings)
This study investigates the construction methodology of large-span cable-stayed tensioned metal thin-sheet structures, introducing the “integrated enclosure and load-bearing” design concept. By applying in-plane prestress, the out-of-plane stiffness of the metal thin sheet is effectively enhanced, enabling it to simultaneously serve as an enclosure and a load-bearing component. Through experimental studies and finite element analysis, the study systematically examines the effects of various construction methods on internal forces and displacements. The tensioning of back cables is identified as the safest and most efficient construction method. Subsequently, through simulations of a three-span structure and tensioning forming tests, the research examines displacement, stress, and cable force distribution patterns, demonstrating that increases in the tensioning level result in corresponding increases in sheet surface stress, cable forces, and displacements. The structure exhibits a concave middle section, upward curvatures at both ends, and outward-leaning end columns. Structural members with lower cable forces show minimal impact on displacement and are therefore identified as suitable targets for design optimization. This study offers a theoretical foundation and practical engineering insights to guide the optimization of design and construction for cable-stayed tensioned metal thin-sheet structures.